Guerra sem fim: mulheres na trilha do direito à terra e ao destino dos filhos (Pará - 1835-1860) - Ferreira, Eliana Ramos (2010)
The thesis GUERRA SEM FIM: MULHERES NA TRILHA DO DIREITO À TERRA E AO DESTINO DOS FILHOS (PARÁ-1835-1860) analysis the strategies and mechanisms, with which groups of women decoded the right and the juridical rules in the historical context after- Cabanagem, in the province of Pará. The research finds support in a diverse documental corpus (land Registers, requirements, official statements, testaments, inventories, newspapers, as well as reports of presidents, ministers and managers of public land distribution) grouped in regional and national archives. The incursion in these historical data accentuates the legal domain, the conflicts and the strategies elaborated by the women. The Land Law Decree of 1850, and the Decree of 1854, opened possibility conditions for the regularization of the ownerships . The administrative mechanisms and their political meanders were examined in the action perspectives of these women. The domain and the land control by women acquired attention. These, in turn, appropriated these instruments in situations of juridical conflicts, and found in them the support, as well as answers (in some circumstances) to their appeals, therefore, a vision of right and a sense of justice. The approach of the social history field, with its theoretical and methodological instruments, allowed the opening of this discussion field about order, conflict, as well as the desire and projects regarding to its sons and daughters and the position of the women in the paraense society of XIX century